The Determining Factors of Quality of Life in Chronic Kidney Disease Patients with Hemodialysisin Hospitals: A Literature Review - Wahyuni, Ni Wayan Sri; Kamaryati, Ni Putu; Rismawan, Made; Suantika, Putu Inge Ruth (Babali Publisher, 2025)
Introduction: Patients with chronic renal failure undergoing hemodialysis often experience a decline in quality of life. This decline is due to challenges in accepting their condition, the physical and emotional impact of treatment, and significant lifestyle changes. Maintaining or improving quality of life is essential for these patients to manage their condition effectively and live well. Methods: This study employed a literature review design, adhering to the PRISMA checklist for study selection. The review utilized five journal databases: ScienceDirect, EBSCO, PubMed, Neliti, and Google Scholar, with keywords aligned with MeSH terms: